THE IMPACT OF PROMOTIONS ON CONSUMER BEHAVIOR - STAN FLORIN ALEXANDRU; PANDURU ANDREI-DORIAN (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
Promotions are a fundamental strategy in marketing, having a significant impact on consumer behavior and purchasing decisions. This article examines how different types of promotions—including markdowns, special offers, loyalty campaigns, and seasonal promotions—influence consumer choices, driving both impulse purchases and brand loyalty. We will explore the psychological reasons behind the attraction to promotions, such as the perceived value and sense of urgency generated by limited-time offers, and discuss the short- and long-term effects on purchasing behavior. In addition, the article will address the role of technology in promoting offers, highlighting how online and social media platforms facilitate consumers' access to information about promotions and their impact on purchase decisions. By integrating industry examples and case studies, we will emphasize the importance of promotions in marketing strategies and in building lasting relationships with consumers, thus demonstrating that promotions are essential not only for increasing sales, but also for maintaining relevance in an increasingly more competitive.